Pemanfaataan Tapak Liman (Elephantopus scaber) Sebagai Obat Tradisional dan Bioaktivitasnya - Silalahi, Marina (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: Elephantopus scaber (ES) or tapak liman has been used by various ethnic groups in Indonesia and other countries as traditional medicine. Objectives: Comprehensive review of ES bioactivity is still limited, especially in the Indonesian language. Research Metodes: The writing of this article is based on a study of literature published on line and off line using several keywords Elephantopus scaber, bioactivities of Elephantopus scaber and uses of Elephantopus scaber. Results: In ethnobotany ES used wound medication, treatment of nephritis, edema, humidity, chest pain, fever, scabies, sores, coughs, tonics, fever, and bronchitis, and asthma. In China, ES leaves have been developed into "tea" to cure various diseases. The bioactivity of ES is anti-bacterial, anti-fungal, anticancer, hepatoprotective, stimulates hair growth, anti-diabetes mellitus, anti-wound, antioxidant, anti-neuroinflamation and overcoming kidney disorders. Conclusion: Deoxyelephantopin is one of the main sesquiterpenes lactones derived from ES has anti-cancer anti-cancer development. The development of ES tea as an anti-cancer needs to be further investigated because this plant is very easy to find in Indonesia.